Activation of Eosinophils Interacting with Bronchial Epithelial Cells by Antimicrobial Peptide LL-37: Implications in Allergic Asthma - Delong Jiao (Nature Portfolio, 2017)
Abstract The role of antimicrobial peptide LL-37 in asthma exacerbation is unclear. Microbial infection, which is the most common inducer of asthma exacerbation, is accompanied by elevated LL-37. The present study found that co-culture of eosinophils and bronchial epithelial cell line BEAS-2B significantly enhanced intercellular adhesion molecule-1 on both cells and CD18 expression on eosinophils upon LL-37 stimulation. IL-6, CXCL8 and CCL4 were substantially released in co-culture in the presence of LL-37. LL-37 triggered the activation of eosinophils interacting with BEAS-2B cells in a P2X purinoceptor 7/epidermal growth factor receptor-dependent manner. Eosinophils and BEAS-2B cells differentially contribute to the expression of cytokines/chemokines in co-culture, while soluble mediators were sufficient to mediate the intercellular interactions. Intracellular p38-mitogen-activated protein kinase, extracellular signal-regulated kinase and NF-κB signaling pathways were essential for LL-37-mediated activation of eosinophils and BEAS-2B cells. By using the ovalbumin-induced asthmatic model, intranasal administration of mCRAMP (mouse ortholog of LL-37) in combination with ovalbumin during the allergen challenge stage significantly enhanced airway hyperresponsiveness and airway inflammation in sensitized mice, thereby implicating a deteriorating role of LL-37 in allergic asthma. This study provides evidence of LL-37 in triggering asthma exacerbation via the activation of eosinophils interacting with bronchial epithelial cells in inflammatory airway.